Validation of an automated dispensing system for subsequent dose dispensing of different radionuclides - T. T. Cao; E. A. Aalbersberg; M. M. Geluk-Jonker; J. J. M. A. Hendrikx (EJNMMI Radiopharmacy and Chemistry, 2024)
Abstract Background Automated dispensing systems (ADSs) for radiopharmaceuticals have been developed to reduce the radiation exposure of personnel, to improve the accuracy of the dispensed dose and to limit the microbiological contamination. However, before implementing such systems, validation according to various applicable guidelines is necessary to ensure safety and quality. Here we present the selection, validation and implementation of the PT459R2 from manufacturer Lynax s.r.o. as a guidance protocol for validation according to GMP and GRPP guidelines. Validation included linearity accuracy and precision of the internal scintillation detector for different isotopes and microbiological validation for aseptic procedures. Results The ADS can dispense accurate doses in the following linear range: 1000–10,000 MBq for lutetium-177, 20–74 MBq for zirconium-89, 100–1000 MBq for gallium-68 and 100–2000 MBq for fluorine-18. The maximum bias is 2.35% and the maximum coefficient of variation is 3.03% which meets the acceptance criteria of < 5%. Furthermore, the ADS does not affects the GMP class A environment in a laminar airflow cabinet and can dispense aseptically. In addition, radiation exposure is acceptable and data integrity is preserved. Conclusion The PT459R2 ADS met all the requirements from our performance qualification and is therefore suitable for daily routine use in our center. Our approach can be used as a guidance for PQ of an ADS in a Radiopharmacy according to GMP and GRPP guidelines.